2014
DOI: 10.1007/s10029-014-1312-y
|View full text |Cite
|
Sign up to set email alerts
|

Positive outcomes with negative pressure therapy over primarily closed large abdominal wall reconstruction reduces surgical site infection rates

Abstract: The data presented in this study demonstrates a potential advantage for adjunctive NPT in patients undergoing AWR. There is an associated decreased incidence in the overall rate of SSI and hernia recurrence with the use of NPT in those patients undergoing AWR. These results show an advantage for adjunctive NPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…Our review found a number of case studies, case series and non‐randomised controlled trials that described ciNPT use. These studies included high‐risk patients with one or more comorbidities who underwent various surgical procedures, including vascular bypass, sternotomy and caesarean section . In 2013, Condé‐Green et al reported that patients undergoing abdominal hernia repairs treated with ciNPT had a lower surgical site occurrence (SSO) rates (22% versus 63%, P = 0·02) and dehiscence (9% versus 38%, P = 0·014) compared with patients treated with wound dressings .…”
Section: Resultsmentioning
confidence: 99%
“…Our review found a number of case studies, case series and non‐randomised controlled trials that described ciNPT use. These studies included high‐risk patients with one or more comorbidities who underwent various surgical procedures, including vascular bypass, sternotomy and caesarean section . In 2013, Condé‐Green et al reported that patients undergoing abdominal hernia repairs treated with ciNPT had a lower surgical site occurrence (SSO) rates (22% versus 63%, P = 0·02) and dehiscence (9% versus 38%, P = 0·014) compared with patients treated with wound dressings .…”
Section: Resultsmentioning
confidence: 99%
“…We found 6 RCTs, [ 6 , 9 , 21 23 ] 3 prospective observational studies, [ 19 , 20 , 24 ] 10 retrospective observational studies, [ 25 34 ] and 1 article [ 35 ] with both retro- and prospective data. In the observational studies, the use of pNPWT was based on the surgeons decision in 6 studies [ 19 , 25 , 27 , 30 , 32 , 33 ] and based on time (before-after) in 8 studies. [ 24 , 25 , 28 , 29 , 31 , 34 36 ] The evidence table with more detailed information is in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…91 Advances in surgical approach, including laparoscopy, intraoperative wound irrigation, the use of wound protectors during an operation, and negative pressure wound therapy (NPWT) systems afterward have also been shown to reduce wound morbidity at follow-up. 22,[92][93][94][95] NPWT (Figure 2) is a technique often employed at the abdominal incision/wound following a general surgery operation that incorporates a foam dressing and suction pump that provides an airtight seal to the wound. NPWT has also been used for the management of ulcers, skin flaps, grafts, and burns.…”
Section: Wound Dressingsmentioning
confidence: 99%